Penanganan Radikalisme Melalui Program Deradikalisasi sebagai Upaya untuk Mencegah Tindak Pidana Terorisme di Indonesia - Pratama Maulidyawanto; Hernawati RAS; Nandang Sambas (Jurnal Hukum Lex Generalis, 2023)
The negative side of radicalism is the embryo of terrorism. The negative side of radicalism is in the form of attitudes that want total revolutionary change through violence and extreme actions. Non-penal efforts of criminal law can be the most powerful effort in dealing with radicalism. Non-penal efforts are based on existing regulations in Indonesia, namely the deradicalization program, but the fluctuating terrorism events that occur in Indonesia are an indication of the ineffectiveness of the deradicalization program carried out by relevant agencies. This is due to the lack of human resources, the lack of infrastructure related to the implementation of the deradicalization program, and the absence of clear arrangements related to the deradicalization program.